Transforming malaysia : dominant and competing paradigms - Milner, Anthony; Abdul Rahman Embong; Tham, Siew Yean. ([s.l.] : Institute of Southeast Asian Studies, 2014)
In the wake of Malaysia's 13th General Election some commentators speak of a sharpening of ethnic politics with Prime Minister Najib blaming a 2Chinese tsunami3 for his government's polling setbacks; others are optimistic about the arrival of a new 2non-racialized form of politics3 and the emergence of 2transethnic solidarity3. This book, which engages with both the race paradigm and its opponents, warns that change is likely to come slowly but is not impossible. Malaysia's race paradigm is a man-made ideological construct one that has been contested in the past, and could realistically be contested in the future. In confronting the continuing challenge of globalization, Malaysians should not neglect the history of ideas and ideology as they search for new options.
Cover, Title,Transforming malaysia : dominant and competing paradigms--Preface, Introduction, TOC,Contents--Preface, Introduction, TOC,List of Table and Figures--Preface, Introduction, TOC,Preface--Preface, Introduction, TOC,Acknowledgements--Preface, Introduction, TOC,List of Contriburors--References, Appendix, Index,Index.
Keywords: Malaysia -- Race relations; Malaysia--Economic policy; Malaysia -- Politics and government; Malaysia -- Foreign relations